Abrupt aggravation of atrioventricular block and syncope in hypertrophic cardiomyopathy. Issue 6 (December 1995) - Tamura, M; Harada, K; Ito, T; Enoki, M; Takada, G
Abstract : A 10 year old girl with hypertrophic cardiomyopathy (HCM) developed high grade atrioventricular (A-V) block unexpectedly, which instantly led to syncope; she required a permanent pacemaker. High grade A-V block, a rare complication of HCM, relates closely to syncope or sudden death in this disease and if progressive the use of cardiac pacing should be considered without delay.